2007
DOI: 10.3102/0002831207306743
|View full text |Cite
|
Sign up to set email alerts
|

Final Reading Outcomes of the National Randomized Field Trial of Success for All

Abstract: Using a cluster randomization design, schools were randomly assigned to implement Success for All, a comprehensive reading reform model, or control methods. This article reports final literacy outcomes for a 3-year longitudinal sample of children who participated in the treatment or control condition from kindergarten through second grade and a combined longitudinal and in-mover student sample, both of which were nested within 35 schools. Hierarchical linear model analyses of all three outcomes for both sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
154
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(165 citation statements)
references
References 53 publications
5
154
0
6
Order By: Relevance
“…We tested whether these students' behavior, particularly the behavior of social referents, could influence other students' perceptions of social norms of conflict and shift overall levels of conflict behavior at the school. In contrast with previous work that randomizes at either the student or the school level (41)(42)(43), the present experiment combined these two approaches. In an experiment conducted over the school year from September 2012 to June 2013, we randomly assigned half of 56 public middle schools (which include students ages 11-15 y old) scattered throughout the state of New Jersey to receive the intervention.…”
Section: Methodsmentioning
confidence: 79%
“…We tested whether these students' behavior, particularly the behavior of social referents, could influence other students' perceptions of social norms of conflict and shift overall levels of conflict behavior at the school. In contrast with previous work that randomizes at either the student or the school level (41)(42)(43), the present experiment combined these two approaches. In an experiment conducted over the school year from September 2012 to June 2013, we randomly assigned half of 56 public middle schools (which include students ages 11-15 y old) scattered throughout the state of New Jersey to receive the intervention.…”
Section: Methodsmentioning
confidence: 79%
“…Multi-year studies of the Success for All elementary program (Madden, Slavin, Karweit, Dolan, & Wasik 1993;Borman et al, 2007) typically find much better outcomes with each successive year of program implementation (Slavin & Madden, 2001). The same may be true of The Reading Edge.…”
Section: Discussionmentioning
confidence: 99%
“…However, comprehension results, although generally positive, were not statistically significant and this is worthy of further research. The largest cluster randomized evaluation of SFA in the United States, by Borman et al (2007), found positive effects of SFA in word-level outcomes in kindergarten and first grade, but comprehension effects did not appear until second and third grades. If the current evaluation were continued for another year, it might also find significant comprehension effects as Borman et al (2007) did.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a large cluster randomized controlled trial in the United States involved a 3-year longitudinal sample of children who participated in the SFA or control condition from kindergarten through the second grade (Borman et al, 2007). Hierarchical linear model (HLM) analysis revealed statistically significant school-level effects of assignment to SFA on literacy outcomes.…”
Section: Previous Research On Sfamentioning
confidence: 99%